Análisis comparativo de contenidos en series con clasificación 16+ y 18+ - Muñoz Almache, Anyeli Yuliza (2020)
The present final report of the complexive examination is linked to the comparison of series contents which are classified according to the ages between 16 and 18 years, which allows comparative research to focus on a sustainable model in terms of similarity. and it differs from what is being shown to young people of the aforementioned ages. The method used to carry out the project was the synthetic analysis of the contents obtained from the Netflix application, because it is the application that is currently trending and due to its range of contents that are exposed to the classification of 16+ and 18 +, it was also analyzed how these foreign contents are regulated and how it is regulated in Ecuador through the Organic communication law. This research does not deviate from the lines implemented within the research mesh of the communication career such as "SUSTAINABLE INVESTIGATIVE JOURNALISM APPLIED TO NEW TECHNOLOGIES".